Deer keds on wild ungulates in northern Italy, with a taxonomic key for the identification of Lipoptena spp. of Europe. Issue 1 (1st November 2019) - Salvetti, M.; Bianchi, A.; Marangi, M.; Barlaam, A.; Giacomelli, S.; Bertoletti, I.; Roy, L.; Giangaspero, A.
Abstract: Deer keds ( Lipoptena spp.) are blood‐sucking ectoparasites of domestic and wild animals, and also accidentally of humans. In Europe, five Lipoptena spp. have been recorded, although the lack of specific taxonomic keys has often led to mistaken identification or to missing data. The present study aimed to develop an identification key of the European species and also to identify Lipoptena spp. found on wild ungulates in northern Italy. In total, 390 hippoboscids were collected from Rupicapra rupicapra, Capreolus capreolus, Cervus elaphus and Ovis aries musimon in an Alpine area of Italy. After morphological identification, 140 specimens were subjected to phylogenetic analysis based on mitochondrial ( CO1 ) and nuclear ( CAD ) gene sequences. Despite the expected presence of slight morphological variations, all specimens examined were identified both microscopically and molecularly as Lipoptena cervi (100% identity for both CO1 and CAD genes). The massive increase in wild ungulate populations can favour the possibility of detecting other species of Lipoptena . The identification keys proposed in the present study may help with monitoring the presence of Lipoptena species, particularly in European countries where this ectoparasite is neglected and for which various data (from diffusion to control methods) are still missing. Abstract : Five species of Lipoptena can be found in Europe. Identification keys for European Lipoptena species are provided for the first time. Lipoptena cervi is the only species identified both microscopically and molecularly in northern Italy.